PENERAPAN ASAS ERGA OMNES DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 30/PUU-XVI/2018 DIKAITKAN DENGAN ASAS NEGATIVE LEGISLATOR - Muchamad Lutfi Hakim; Rasji . (Fakultas Hukum Universitas Tarumanagara, 2018)
The problem began because there was an Application to Judicial Review Article 182 Letter l specifically in the phrase